A közúti áruszállítás károsanyag-kibocsátásának csökkentési lehetőségei a járműgyártó szemszögéből - Mihály, László; Miller, György (Acta Carolus Robertus, 2011)
Since the transport sector is responsible for almost 20 per cent of the exhaust emissions in the world, continuous development and regulations are essential. While there are full shelves in shops, the environmental load of transportation is inevitable. If pollution as such cannot be avoided, we must reduce its rate. This dissertation focuses on the various ways and technologies that can help reduce the rate of exhaust emissions and it also takes a look at the good practice at Scania heavy trucks manufacturer. Our research includes the examination of people involved in transportation and their possible relationships which could help reduce the rate of environmental load. Conclusions gained from having looked at the relationships of people involved are complemented by return calculation tests. These calculations verify that reducing exhaust emissions does not necessarily mean increase in expenses.
Keywords: environmental protection; exhaust; environment system